THE INFLUENCE OF COGNITIVE DEVELOPMENT OF PRESCHOOL CHILDREN (Scientific journal of the Fergana State University, 2024)
The article examines the effects of bilingualism on the cognitive development of bilingual language learners. This article provides information on how bilingualism, that is, a bilingual environment, affects the mental and speech development of children. The article describes how the bilingual educational environment affects children's understanding of thought content, development of speech, creativity, and conceptual thinking. The age and learning mechanisms of bilingualism in language learning, the stages of the process of acquiring two languages, and the impact of a bilingual environment on children's intellectual and emotional development are analyzed. They have been studied by many researchers and fully described how bilingualism affects children's cognitive development and communicative competence.